ذو القرنين من خلال النصوص السماوية والمصادر المادية - قواسم,بشرة (University of Eloued جامعة الوادي, 2024)
ملخص الدراسة بالعربية: استهدف هذه الدراسة العلاقة بين التوافق الأسري وجودة الحياة لدى الأسر بولاية الوادي، ومعرفة إن كانت هناك فروق بين أفراد العينة في المتغيرين (التوافق الأسري وجودة الحياة) والتي يمكن أن تعزى إلى الجنس (ذكر / أنثى) . شملت عينة البحث (49 أسرة من أسر ولاية الوادي) تمادت (20 منهم ذكور و29 إناث). واستخدم في الدراسة مقياسان لغرض جمع البيانات اللازمة وهما: مقياس التوافق الأسري لمحمد عبد الحميد 1986، ومقياس جودة الحياة رنا فاضل عباس الجنابي 2023. تمت معالجة البيانات إحصائيا باستخدام البرنامج الإحصائي (Spss) الذي سمح بتطبيق الأدوات الإحصائية التالية: ارتباط (T_TEST) لعينة واحدة، معامل الارتباط برسون، وتوصلت الدراسة الى جملة من النتائج ابرزها: _ يتمتع الأسر بمستوى متوسط من جودة الحياة. _ وجود علاقة ارتباطية ذات دلالة إحصائية بين التوافق الأسري وجودة الحياة لدى الأسر بولاية الوادي. _ لا توجد فروق ذات دلالة إحصائية في جودة الحياة تبعا لمتغير الجنس (ذكور _ إناث) . Abstract: Among the most important stories of the Holy Qur’an that inspire the nation is the story of “Dhul-Qarnayn,” which was mentioned in Surat Al-Kahf. It was mentioned in sixteen verses of the surah from verse (83) to verse (98). Interpretations have agreed that the reason for the revelation of these verses was the question of the Jews when they wanted to test the Messenger. – May God bless him and grant him peace – in his prophecy, and the revelation came to him to answer their question, which suggests that he was an important figure for them and was circulated in the heavenly texts revealed in their time, as studies indicate that he The story of Dhu al-Qarnayn was previously mentioned in the Torah as a righteous leader. He was called Logarnaim or the owner of the two horns in the Book of Daniel, which means Cyrus the Great, while he was mentioned in the First Book of Maccabees as Alexander the Great, but the book never touched on an attempt to link them together. Cyrus the Great was also mentioned in The Old Testament, such as the Book of Ezra, the first chapter, the Book of Daniel, the sixth chapter, and the Book of Isaiah in the forty-fourth and forty-fifth chapters, and the Book of Isaiah described him as the shepherd of the Lord. The people of interpretation disagreed about Dhul-Qarnayn, and it was said: He was a king, and it was said: He was a prophet, and it was said: He was a king. The Qur’an mentioned that Dhul-Qarnayn God empowered him on earth and gave him means, so he roamed the easts and wests of the earth, calling for faith in God, following the path of justice in reward and punishment according to the principle of choice, and his story was associated with Gog and Magog.They were two nations that wreaked havoc on the earth, so a dam was built to prevent their appearance. They were mentioned in the Torah (Old Testament) in the Book of Genesis within the genealogies found in the book. They were also mentioned in the Book of Ezekiel in more detail, and we also find their mention in the Gospel (New Testament) in the Book of Revelation. Opinions differed about the location of the dam’s construction. The character of Dhul-Qarnayn sparked much controversy and disagreement among commentators, historians, researchers, philosophers, and anthropologists, past and present, in determining his identity, and there was much contradiction and disagreement among them about it. Some of them believe that he is Alexander the Great, some of them attribute it to the Himyarite king al-Saab, and some of them favor it. To the Persian King Cyrus the Great. Despite the many studies and research that have been written on this subject, they have not reached the stage of certainty.In revealing the identity of this character and confirming one of the many historical figures nominated to be Dhul-Qarna
Keywords: قران الكريم ذو القرنين; مصادر سماوية; توراة; The Holy Qur’an; Dhul-Qarnayn; heavenly sources; the Torah